Effects Of Sunlight Exposure For Treatment of Tuberculosis : Literature Review - Wijaya, Liza Novitasari; Makiyah, Sri Nabawiyati Nurul (Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Background: Tuberculosis is a contagious infectious disease caused by Mycobacterium. Tuberculosis which can attack various organs, especially the lungs. It is necessary to study the effectiveness of sunlight therapy and the vitamin D diet as supporting tuberculosis treatment.Objective: This study aimed at investigating the literature for of provision of sunlight in tuberculosis patients.Method: This library review uses a database with the electronic search on Ebsco, ClinicalKey, Google Scholar, and ScienceDirect published in 2016 - 2019.Results: Six articles were used to review. The article discusses vitamin D deficiency as a causative factor for tuberculosis, the effectiveness of clinical treatment in a sanatorium using vitamin D and the use of sunlight as a treatment for tuberculosis in the days before the discovery of antibiotics.Conclusion: Sun exposure has been shown to provide a clinical improvement in patients by providing comfort and improving moods that are unable to increase the elimination of bacteria in the lungs.Conclusion: This therapy provides clinical improvement to the patient and provides a calm sensation and improves mood even though it has not been able to eliminate the bacteria in the lungs until anti-TB drugs are found and this sunlight therapy is forgotten.